Suksesi Hutan Mangrove Pulau Kaget dan Pulau Tempurung melalui Pendekatan Ekologi Spasial 2005-2025: Mangrove Forest Succession on Kaget and Tempurung Islands (2005–2025): A Spatial Ecology Approach - Rosadi, Hadi; Shiba, Yasinta Nur; Hadi, Wirawan Noor (Fakultas Kehutanan Universitas Jambi, 2026)
ABSTRACT Mangrove forests in the Barito River estuary exhibit dynamic changes that occur alongside land accretion processes and variations in hydrological conditions. This study aims to analyze the relationship between mangrove canopy density and water dynamics using the Combined Mangrove Recognition Index (CMRI) and the Modified Normalized Difference Water Index (MNDWI) on Pulau Kaget and Pulau Tempurung during the period 2005–2025. The analysis was conducted using multi-temporal Landsat imagery at five-year intervals, including CMRI and MNDWI mapping, change detection analysis, time-series evaluation, and Pearson correlation testing. The results indicate an increase in mean CMRI values on both islands, with the most pronounced increase observed on Pulau Tempurung, where CMRI values more than doubled compared to initial conditions. In contrast, mean CMRI values on Pulau Kaget tended to stabilize after 2010 due to limited space for further accretion. MNDWI analysis shows a reduction in water area on both islands, with land proportion increasing from 82.98% to 88.82% on Pulau Tempurung and from 89.77% to 93.55% on Pulau Kaget. Correlation analysis reveals a negative relationship between CMRI and MNDWI (r = −0.596), indicating that increasing mangrove density is associated with land accretion processes. These findings confirm that the integration of CMRI and MNDWI is effective for monitoring the spatial–temporal ecological and geomorphological dynamics of mangrove ecosystems. Keywords: barito estuary, mangrove forest, spatial ecology, vegetation succession ABSTRAK Hutan mangrove di muara Sungai Barito memiliki dinamika yang berlangsung seiring dengan proses akresi lahan dan perubahan kondisi perairan. Penelitian ini bertujuan menganalisis hubungan kerapatan mangrove dan dinamika perairan menggunakan pendekatan indeks CMRI (Combined Mangrove Recognition Index) dan MNDWI (Modified Normalized Difference Water Index) pada Pulau Kaget dan Pulau Tempurung selama periode 2005–2025. Analisis dilakukan menggunakan Citra Landsat 5 TM serta Landsat 8/9 OLI/TIRS dengan interval lima tahunan, meliputi pemetaan CMRI, MNDWI, deteksi perubahan, analisis deret waktu, serta uji korelasi Pearson. Hasil menunjukkan peningkatan rerata CMRI pada kedua pulau, dengan peningkatan paling menonjol terjadi di Pulau Tempurung yang meningkat lebih dari dua kali lipat dibandingkan kondisi awal periode pengamatan. Data pada Pulau Kaget, rerata CMRI cenderung stabil setelah tahun 2010 seiring terbatasnya ruang akresi. Analisis MNDWI menunjukkan penurunan luasan perairan pada kedua pulau, di mana persentase lahan meningkat dari 82,98% menjadi 88,82% di Pulau Tempurung dan dari 89,77% menjadi 93,55% di Pulau Kaget. Uji korelasi menunjukkan hubungan negatif antara CMRI dan MNDWI (r = −0,596), yang mengindikasikan keterkaitan antara peningkatan kerapatan mangrove dan proses akresi lahan. Temuan ini menegaskan bahwa integrasi CMRI dan MNDWI efektif untuk memantau dinamika ekologis dan geomorfik mangrove secara spasial-temporal. Kata kunci: ekologi spasial, hutan mangrove, muara barito, suksesi vegetasi